Identification of a Novel Intronic Mutation in VMA21 Associated with a Classical Form of X-Linked Myopathy with Autophagy - Bardhan, Mainak; Polavarapu, Kiran; Baskar, Dipti; Preethish-Kumar, Veeramani; Vengalil, Seena; Nashi, Saraswati; Ganaraja, Valakunja H.; Sharma, Dinesh; Kulanthaivelu, Karthik; Nandeesh, B.N.; Nalini, Atchayaram (Global Medical Genetics, 2024)
Introduction VMA21-related myopathy is one of the rare forms of slowly progressive myopathy observed in males. Till now, there have been only a handful of reports, mainly from Europe and America, and two reports from India.Method Here, we describe a case of genetically confirmed VMA21-associated myopathy with clinical, histopathological, and imaging features with a list of known VMA21 mutations.Results A 29-year-old man had the onset of symptoms at 18 years of age with features of proximal lower limb weakness. Muscle magnetic resonance imaging showed the preferential involvement of vasti and adductor magnus. A biopsy of the left quadriceps femoris showed features of autophagic vacuolar myopathy with vacuoles containing granular eosinophilic materials. In targeted next-generation sequencing, hemizygous mutation in the 3′ splice site of intron 2 of the VMA21 gene (c.164–7 T > A) was identified and confirmed the diagnosis of X-linked myopathy with excessive autophagy.Conclusion This report expands the phenotypic and genotypic profile of VMA21-related myopathy, with a yet unreported mutation in India.
Keywords: VMA21-related myopathy; autophagy; muscle MRI